Los límites y las consecuencias reales del discurso jurídico de la autonomía privada de la voluntad en el individuo (2018)
This article arises from the research project entitled “The Implications of the legal discourse in the individual”, attached to the National Seedbed in Hermeneutics and Legal Arguments of the University of Santo Tomás, Medellín, Colombia. This project proposes to analyse the need that humanity has had to create legal norms regulating contractual relations between social individuals and how they have managed to determine and orient man’s actions, since they have been accepted or welcomed by human societies through a covenant or social contract and to the generation of a mass thinking in order to find social peace and find a balance of powers, both between relations with the State and among individuals. It is important to mention that the individual is conditioned in his work not only by the awareness of the norm that dictates his model of action, but also by the contents of his unconscious. It is why it is necessary to pose the relationship between the norm and the social behavior of men, which manifests itself through the human transactions resulting from the expression of the private autonomy of the parties.